The Independent Biological Activity of Bacillus thuringiensis Cry23Aa Protein Against Cylas puncticollis - Hernández-Martínez, Patricia; Khorramnejad, Ayda; Prentice, Katterine; Andrés-Garrido, Ascensión; Vera-Velasco, Natalia Mara; Smagghe, Guy; Escriche, Baltasar (Frontiers in Microbiology, 2020)
The Cry23Aa/Cry37Aa proteins from Bacillus thuringiensis (Bt) have been described toxic to Cylas puncticollis larvae. In general, it is believed that The Cry23Aa/Cry37Aa proteins from Bacillus thuringiensis (Bt) have been described toxic to Cylas puncticollis larvae. In general, it is believed that Cry23Aa and Cry37Aa act jointly to exert the insecticidal activity, while there is no evidence of their toxicity individually. Therefore, in the present study, the contribution of each protein in the insecticidal activity towards C. puncticollis larvae has been assessed. The results showed that both proteins were toxic for C. puncticollis larvae when tested individually. Contrary to what was claimed previously, our results suggest that the presence of both proteins is not necessary to exert toxicity against C. puncticollis larvae. Also, the binding behavior of Cry23Aa protein to midgut receptors of C. puncticollis larvae has been determined. According to our results, Cry23Aa binds to C. puncticollis BBMV specifically and independently of Cry37Aa. Due to the lack of common binding sites, Cry23Aa can be pyramided with Cry3Aa protein for better management of C. puncticollis.